Study on Calculation of Cross-section Area of River Based on Analysis Method of Mid-point Distance Section - DANG Xicheng; LUO Yi; WANG Haiyan; LI Rong (Renmin Zhujiang)
The cross-section area is one of the key factors in flow measurement by velocity area method,and its calculation accuracy is directly related to the accuracy of flow measurement.Due to the complexity and diversity of the river section,the existing software algorithm cannot accurately judge the real position of the river flow through the large section data,resulting in the extraction error of the range of the cross section and the vertical depth.Therefore,with computer programming technology,this paper puts forward the analysis method of river mid-point distance section for identifying the position of river flow and judging the type of section,such as single section and compound section,extracting the water's edge and vertical line,and calculating the area.The application shows that the software can accurately analyze the river flow position under different hydraulic conditions by this method,and calculate the river cross-section area,achieving the purpose of algorithm design.This method can be widely used in automatic hydrological detection equipment or hydrological analysis software to improve the analysis ability of the equipment or software for cross-section flow area of river.